EVOLUTION OF SOCIAL PHILOSOPHICAL STUDIES OF SOCIAL INEQUALITYPROBLEM: ANTIQUE AND MEDIEVAL EPOCHS - Абисова, М. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2014)
The article is devoted to the analysis of evolution of the idea of social inequality in antique and medieval social philosophical theories.